Digital Clock with Speech Recognition - Timothy Nathaniel Halim; Antonius Suhartomo (Journal of Electrical And Electronics Engineering, 2016)
One of the functions of a digital clock is to wake us from sleep, in order to perform the activities as scheduled. Technological developments allow the incorporation of digital clock function with voice recognition, making it easier for us to do as to turn off the alarm without having to press a button, asking what time without having to view the display, and so forth. From these points of view, the idea to design and to implement a “Digital Clock with Speech Recognition” came up. This experiment concentrates in designing the hardware and the software that will work as an integration system of circuit that has the digital clock function. The circuit also has other function which is the speech recognition. Through this function, the user of the circuit will be able to record his or her voice in the form of short words. After the recording, the user can start to order the circuit to recognize his or hervoice. Finally, both digital clock and speech recognition functions are combined to work together, therefore when there is a voice recognized, then the speech recognition circuit will send a digital signal to the digital clock circuit to be processed as an input signal to operate certain digital clock function.Keywords: digital clock, speech recognition, microcontroller ATmega8535